Contribuição ao conhecimento químico de plantas medicinais do Nordeste: Bauhinia pentandra (BONG.) D.DIETR. e Bauhinia monandra KURZ - Almeida, Macia Cleane Soares de (2015)
This work describes the phytochemical investigation of the species Bauhinia pentandra (Bong.) D.Dietr. and Bauhinia monandra Kurz, belonging to the Fabaceae family. The chemical composition of the essential oil from the leaves dried and fresh B. pentandra, obtained by hydrodistillation and solid phase microextraction (SPME), was determined by GC/MS. The major constituent of the oil obtained from the hydrodistillation technique was -caryophyllene in the dried leaves, and phytol in the fresh ones, whereas the major compound of the oil obtained by SPME technique was -caryophyllene in the dried leaves, and 2-ethylhexyl and homomenthyl salicylates in the fresh ones. The fatty acids present in the hexanic extracts were identified by GC/MS, presenting as major components palmitic, linolenic and stearic acids in B. pentandra and linolenic and linoleic acids in B. monandra. The chemical study of the ethanol extract of leaves of B. pentandra allowed the isolation and characterization of mixtures of fatty acids (palmitic and stearic), steroids (sitosterol and stigmasterol), phenylacetic acid derivatives (2,4-dihydroxyphenylacetic acid, 2,4-dihydroxyphenylacetic acid ethyl ester and 2,4-dihydroxyphenylacetic acid methyl ester), plus a mix of 6-hydroxybenzofuran-2(3H)-one and 1-(3',4'-dimethoxyphenyl)-2-propanol, and a mixture of a cyanoglucoside (dasycarponin) and ethyl glucopyranoside. It was isolated and characterized also a methyl inositol derivative ((+)-3-O-methyl-D-chiro-inositol) and two lactones, 7-epi-griffonilide (not described) and dasycarponilide. In ethanolic extract of leaves of B. monandra were isolated and identified the ethyl palmitate and ethyl stearate in mixture, the -tocopherol (vitamin E), the diterpene (phytol) and two cyanoglucosides, (2R,3S,4R,5R,6S)-(Z)-6-(β-D-glucopyranosiloxy)-2,3,4,5-tetrahydroxycyclohexylidene- acetonitrile (unpublished) and didemethylsimmondsin. The compounds were isolated by classic chromatographic techniques and HPLC, and their structures were determined by spectroscopic analysis (1H NMR, 13C NMR, FT-IR and MS), as well as compared with data from the literature. The extracts were evaluated as total phenols content, antioxidant activity, nematicide and anticholinerterase.